European Critical Infrastructure Protection - Lazari, Alessandro (Springer eBooks, 2014)
The recent European Council Directive 114/08 requested the EU Member States to perform an assessment aimed at the identification and designation of the so-called European Critical Infrastructures (ECI). Every analysis of the results of the "first round" of identifications and designations has only taken into account the numbers of ECIs effectively designated, consequently leaving aside all of the other elements related to this important path towards a harmonized vision of the "European Security." This work, with its unprecedented approach, focuses on the elements that have maximized or frustrated the ambitious European objectives and on the issues that might have prevented the directive reaching its full potential. Furthermore, the study offers an in-depth perspective on the lessons learned-including those that can be learned from the "U.S." pre-post 9/11 CIP policies-as well as an assessment of the state of play of the Member States after the implementation of the directive, together with predictions for future challenges.